Sex-lethal in neurons controls female body growth in Drosophila. Issue 2 (3rd April 2018) - Sawala, Annick; Gould, Alex P.
ABSTRACT: Sexual size dimorphism (SSD), a sex difference in body size, is widespread throughout the animal kingdom, raising the question of how sex influences existing growth regulatory pathways to bring about SSD. In insects, somatic sexual differentiation has long been considered to be controlled strictly cell-autonomously. Here, we discuss our surprising finding that in Drosophila larvae, the sex determination gene Sex-lethal ( Sxl ) functions in neurons to non-autonomously specify SSD. We found that Sxl is required in specific neuronal subsets to upregulate female body growth, including in the neurosecretory insulin producing cells, even though insulin-like peptides themselves appear not to be involved. SSD regulation by neuronal Sxl is also independent of its known splicing targets, transformer and msl-2, suggesting that it involves a new molecular mechanism. Interestingly, SSD control by neuronal Sxl is selective for larval, not imaginal tissue types, and operates in addition to cell-autonomous effects of Sxl and Tra, which are present in both larval and imaginal tissues. Overall, our findings add to a small but growing number of studies reporting non-autonomous, likely hormonal, control of sex differences in Drosophila, and suggest that the principles of sexual differentiation in insects and mammals may be more similar than previously thought.